Gynecological/Obstetric Background and Rheumatoid Arthritis: A Cross-sectional Study in Brazilian Patients - Cavalcante, Anauá Fernanda dos Santos; Martin, Patrícia; Skare, Thelma Larocca (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2021)
Objective To study a sample of rheumatoid arthritis (RA) patients for their gynecological/obstetric history and compare them to controls to determine their influences on number of pregnancies, menarche, menopause and reproductive years following RA onset.Methods This is a cross-sectional study of 122 RA patients and 126 controls. Patients and controls were questioned about age of menarche, age of menopause, number of pregnancies and abortions. Reproductive years were calculated as the difference between age at menopause and age at menarche. For comparison, we used the Mann-Whitney, unpaired t, chi-squared, and Spearman tests. The adopted significance was 5%.Results In the RA patients with disease beginning in the postmenopausal years, the period of reproductive years (age at menopause – age of menarche) showed a positive correlation with age at disease onset (rho = 0.46; 95% confidence interval [CI] = 0.20–0.55 with p = 0.0008). The number of pregnancies was higher in patients with postmenopausal disease onset when compared with those with premenopausal disease onset (median of 3 with interquartile range [IQR] = 2–4 versus median of 2 with IQR = 1–3; p = 0.009), and RA patients had more pregnancies than controls (p = 0.0002).Conclusion The present study shows that, in our population, the duration of reproductive years and the number of pregnancies are linked to the onset of RA.
Keywords: rheumatoid arthritis; pregnancies; menarche menopause; postmenopause